A line passes through the point (-3, -3) and has a slope of .
What is the equation of the line?

Question

Asked 9/15/2014 9:22:01 AM

Updated 9/16/2014 12:11:30 AM

1 Answer/Comment

s

Question

Asked 9/15/2014 9:22:01 AM

Updated 9/16/2014 12:11:30 AM

1 Answer/Comment

Rating

8

f(x) = 4x - 3,

f(x) - 1 = 4x - 3 - 1 = 4x - 4

f(x) - 1 = 4x - 3 - 1 = 4x - 4

Added 9/16/2014 12:11:30 AM

This answer has been confirmed as correct and helpful.

Divide the following polynomial, then place the answer in the proper location on the grid.
(16x^2 -25) (4x + 5)

Question

Not Answered

Updated 9/8/2014 8:31:38 AM

1 Answer/Comment

(16x^2 -25) ÷ (4x + 5)

= (16x^2/4x+5) - (25/4x+5)

= 4x - 5

= (16x^2/4x+5) - (25/4x+5)

= 4x - 5

Added 9/8/2014 8:31:38 AM

This answer has been confirmed as correct and helpful.

Divide the following polynomial, then place the answer in the proper location on the grid. Write your answer in order of descending owers of x.
(6x^3 + 11x^2 - 4x - 4)/(3x - 2)

Question

Updated 9/10/2014 8:41:01 AM

1 Answer/Comment

(6x^3 + 11x^2 - 4x - 4)/(3x - 2)

= (6x^3/3x - 2) + (11x^2/3x - 2) - (4x/3x - 2) - (4/3x - 2)

= 2x^2 + 5x + 2

= (6x^3/3x - 2) + (11x^2/3x - 2) - (4x/3x - 2) - (4/3x - 2)

= 2x^2 + 5x + 2

Added 9/10/2014 8:41:01 AM

This answer has been confirmed as correct and helpful.

Divide the following polynomials, then place the answer in the proper location on the grid. Write answer in descending powers of x.
(27x^4 - 18x^3 + 9x^2) ÷ 3x

Question

Updated 9/12/2014 11:15:06 AM

1 Answer/Comment

(27x^4 - 18x^3 + 9x^2) ÷ 3x

= (27x^4/3x) - (18x^3/3x) + (9x^2/3x)

= 9x^3 - 6x^2 + 3x

= (27x^4/3x) - (18x^3/3x) + (9x^2/3x)

= 9x^3 - 6x^2 + 3x

Added 9/12/2014 11:15:06 AM

This answer has been confirmed as correct and helpful.

Divide the following polynomials, then place the answer in the proper location on the grid. Write answer in descending powers of x.
(12x3 - 11x2 + 22x - 5) (4x -1)

Question

Updated 9/12/2014 11:13:46 AM

1 Answer/Comment

(12x^3 - 11x^2 + 22x - 5) ÷ (4x - 1)

= (12x^3/4x - 1) - (11x^2/4x - 1) + (22x/4x - 1) - (5/4x - 1)

= 3x^2 - 2x + 5

= (12x^3/4x - 1) - (11x^2/4x - 1) + (22x/4x - 1) - (5/4x - 1)

= 3x^2 - 2x + 5

Added 9/12/2014 11:13:46 AM

This answer has been confirmed as correct and helpful.

Evaluate |-10| - |-8|
-2
2
18

Question

Updated 9/11/2014 9:28:11 AM

1 Answer/Comment

|-10| - |-8| = 10 - 8 = 2

Added 9/11/2014 9:28:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/11/2014 9:31:53 AM]

32,570,310

questions answered

There are no comments.